Intravenous lidocaine and ketamine combined infusion in chronic pain relief: a follow-up study - A. A. N. Samanthi; S. S. Ranasinghe; C. Mettananda (Asian Journal of Internal Medicine, 2025)
Introduction: Chronic pain is a common problem worldwide. It is a significant cause of disability and is challenging to treat. Intravenous lidocaine and ketamine combined infusion is a novel treatment strategy. Data on the efficacy and acceptability of this in South Asia is sparse. We studied the same in a cohort of Sri Lankans with chronic pain resistant to usual medications. Methods: We studied all the patients with chronic pain who were not responding to routine oral analgesic medications and underwent the above treatment at the Pain Clinic of Colombo North Teaching Hospital Ragama from March to August 2022. We followed them up from the intervention date (baseline) to 1-month post-intervention at 24-hours, 2-week, and 1-month intervals. Patients were interviewed by a medical graduate using an interviewer-administered questionnaire. Data on demographics, past medical history, and pain intensity were gathered at baseline. Pain intensity was measured at baseline and 24 hours, 2 weeks, and 1 month post-intervention, while physical and psychosocial deficits were assessed at baseline and 1-month using Brief Pain Inventory Short Form (BPISF) and compared. Results: A total of 29 patients, 8(27.6%) of them males, with a mean age (±SD) of 53±13.3 years were studied. The mean pain score at baseline, 7 ±1.5, reduced to 3 ±1.5 at 1 month (p = 0.001). The change in BPISF parameters from baseline to 1-month post-intervention were as follows: physical deficit 5±2.0 to 3±1.9(p= 0.001), sleep 6±2.3 to 3±1.9 (p= 0.001), enjoyment of life 5±2.1 to 3±1.9(p=0.001), mood 5±2.0 to 3±1.8 (p=0.001) and sexual relationship 5±2.1 to 3±1.9 (p =0.001). There were no major adverse effects of treatment. The majority, 24(80%) were satisfied with the intervention. Conclusion: Intravenous ketamine and lidocaine combined infusion maintained sustained pain relief and improved related parameters in the majority of this Sri Lankan cohort with resistant chronic pain.